فعالية استخدام وسيلة فيديو اليوتوب في إلقان التراكيب لدى الطلاب الصف العاشر في مدرسة نور الهداية الثانوية الإسلامية سيماطوركيس راوو الجنوبية - هيرياني, إيلسا; ريزال, إيكا; ديوي, يلفي; حسنة, نور (Darul Yasin Al Sys, 2023)
One of the problems is that the teacher used the traditional teaching method and did not use the modern teaching method in teaching the Arabic languge, especially in teaching grammar, so the author wants to try the youtube video method in Arabic language especially teaching grammar. As for the research objectives, it is to find out the effectiveness of using the youtube video in mastering the compotions of tenth grade students in the department of Arabic language education, college of education and educational sciences, state Islamic University of Bukittinggi. In this thesis, the author uses experimental quantitative approach, designing with a type design eksperimental. The writer takes the research sample 64 people. 31 in the experimental class and 33 in the control class. The research group is placed at random and gives the post-test. The author concluded that there is a difference between students who teach compositions using the means of youtube video dan syuras. The experimental class had an average score of 72,58 for the pre-test, and an average for the post-test 84,75. In the control class, the average score for the pre-test 74,74 and the average score for the post-test 80,75. The effectiveness of using the youtube video tool in mastering the compositions of the students of the tenth grade in nur al hidayah Islamic secondary school, shasmatorkis, Rewar, South. Therefore, the hypothesis is accepted (2,737 is greater than 1,998). What is meant is that there is an effective use of the youtube video in mastering the compositions.